Eliciting private information with noise: The case of randomized response - Andreas Blume; Ernest K. Lai; Wooyoung Lim (Bielefeld University, Center for Mathematical Economics (IMW), 2013)
The paper formalizes Warner's (1965) randomized response technique (RRT) as a game and implements it experimentally, thus linking game theoretic approaches to randomness in communication with survey practice in the field and a novel implementation in the lab. As predicted by our model and in line with Warner, the frequency of truthful responses is significantly higher with randomization than without. The model predicts that randomization weakly improves information elicitation, as measured in terms of mutual information, although, surprisingly, not always by RRT inducing truth-telling. Contrary to this prediction, randomization significantly reduces the elicited information in our experiment.
urn:nbn:de:0070-pub-26752412
Keywords: C72; C92; D82; D83; 330; Randomized Response; Lying Aversion; Stigmatization Aversion; Mutual Information; Laboratory Experiments